KAJIAN SIFAT FISIK, KIMIA, DAN MIKROBIOLOGI BEBERAPA JENIS DAUN PISANG SEBAGAI BAHAN KEMASAN TRADISIONAL PADA LAMA BLANSIR YANG BERBEDA - Anom Sutrisna Wijaya, I Made; Apriadi Aviantara, I Gusti Ngurah; Retno Pebrianto, Hervin (Agrotekno; Vol 13, No.2 Agustus 2007, 2014)
The objectives of this research were to study the physical, chemical, and microbiology properties of Banana Leaf as traditional packaging materials at severals length of blanching time, and to determine the type of banana leaf which has the best packaging materials properties. Five types of banana leafs were observed and treated by steam blanching for 2, 4, and 6 minutes. The parameters observed included tensile strength (ASTM D-826), tear strength (ASTM D-687) moisture permeability (desican method), gas permeability (pressure increased method), porosity (ASTM D-726), thickness, weight per surface area, moisture content, oil and acid resistent, and total microbes. The results indicated that different type of banana leaf had different properties, and blanching treatment had significant effect on tensile strength, tear strength, porosity, thickness, weight per surface area, misture content, oil and acid resistant, and total microbes. The type of banana leaf that had the best properties as traditional packaging materials was “pisang kepok” that blanching for 2-4 minutes.
Keywords: traditional packaging materials, banana leaf, blanching